Improvement of teaching economic disciplines to medical students by updating the competency based approach and teaching methods - Galina Vladimirovna Kadakoeva; Ruslan Aslanovich Chemso (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research is due to the need for formation and development of economic thinking among medical students in the implementation of the modern educational paradigm, implying a competence based approach to higher education and compliance of educational programs to the world quality standards. In the implementation of the Federal state educational standard of higher medical education the problem of economic competencies formation in medical students is relevant. Updating the competence based approach to teaching economic disciplines in medical higher educational institutions, as well as expansion of forms and teaching methods, taking into account the above mentioned competencies will facilitate the decision of this problem. The purpose of the research is to update the competence based approach to teaching economic disciplines to medical students. In the research the following methods were used: formalized analysis, analytical method, systematization method and data synthesis. The results of the research: the authors have created a list of competencies to implement in the process of teaching economic disciplines to medical students, as well as systematized and actualized active and passive methods of teaching economic disciplines in accordance with the competence based approach. Key findings: Modernization of higher education, taking into account the requirements of Federal state educational standards of new generations, also entails adapting the principles of competences of future specialists to a dynamically developing external environment. The proposed list of competencies can be used by teachers of specialized departments of higher educational institutions in the process of drawing up working programs of disciplines and directly in teaching economic disciplines in order to improve the quality of the educational process.